2022
DOI: 10.1038/s41467-021-27803-6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycolate phosphatase homologs act as glycerol-3-phosphate phosphatase to control stress and healthspan in C. elegans

Abstract: Metabolic stress due to nutrient excess and lipid accumulation is at the root of many age-associated disorders and the identification of therapeutic targets that mimic the beneficial effects of calorie restriction has clinical importance. Here, using C. elegans as a model organism, we study the roles of a recently discovered enzyme at the heart of metabolism in mammalian cells, glycerol-3-phosphate phosphatase (G3PP) (gene name Pgp) that hydrolyzes glucose-derived glycerol-3-phosphate to glycerol. We identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 78 publications
3
15
0
Order By: Relevance
“…The cellular toxicity caused by the accumulation of G3P appears to be a phenomenon shared by both prokaryotes and eukaryotes, as the negative effects of excess G3P on growth have been observed in E. coli ( 9 , 48 ), S. cerevisiae ( 10 ), C. glutamicum ( 11 ), M. tuberculosis ( 49 ), and C. elegans ( 50 ). Moreover, HAD-like G3PPs that dephosphorylate G3P to glycerol and prevent an accumulation of G3P have been identified in S. cerevisiae ( 10 ), C. glutamicum ( 11 ), and C. elegans ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular toxicity caused by the accumulation of G3P appears to be a phenomenon shared by both prokaryotes and eukaryotes, as the negative effects of excess G3P on growth have been observed in E. coli ( 9 , 48 ), S. cerevisiae ( 10 ), C. glutamicum ( 11 ), M. tuberculosis ( 49 ), and C. elegans ( 50 ). Moreover, HAD-like G3PPs that dephosphorylate G3P to glycerol and prevent an accumulation of G3P have been identified in S. cerevisiae ( 10 ), C. glutamicum ( 11 ), and C. elegans ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular toxicity caused by the accumulation of G3P appears to be a phenomenon shared by both prokaryotes and eukaryotes, as the negative effects of excess G3P on growth have been observed in E. coli ( 9 , 48 ), S. cerevisiae ( 10 ), C. glutamicum ( 11 ), M. tuberculosis ( 49 ), and C. elegans ( 50 ). Moreover, HAD-like G3PPs that dephosphorylate G3P to glycerol and prevent an accumulation of G3P have been identified in S. cerevisiae ( 10 ), C. glutamicum ( 11 ), and C. elegans ( 50 ). In the present study, we identified and characterized the phosphatases PA0562 and PA3172 in P. aeruginosa PAO1, and the overexpression of PA0562 and PA3172 was found to alleviate G3P-induced growth inhibition, whereas the knockout of these two phosphatases potentiated the inhibitory effects of G3P ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We earlier discovered a novel mammalian metabolic enzyme, lying at the heart of intermediary metabolism, Gro3P phosphatase (G3PP), and demonstrated that G3PP directly converts part of the excess glucose-derived Gro3P to less toxic glycerol, which leaves the cell [ 18 ]. We named this novel metabolic pathway the glycerol shunt that possibly helps in glucodetoxification in pancreatic β-cells [ 20 ] and demonstrated that G3PP-glycerol shunt pathway confers better healthspan and lifespan in C. elegans [ 21 ]. Hydrolytic control of intracellular Gro3P by G3PP adds another layer of metabolic regulation that was not recognized previously in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…As the central metabolite at the crossroads of fat and the carbohydrate metabolism, Gro3P has been found in mammals to be directly converted to glycerol in the presence of glycerol-3-phosphate phosphatase (G3PP) (encoded by phosphoglycolate phosphatase , abbreviated as Pgp ) [ 62 ]. Surprisingly, three Pgp homologues have recently been identified in C. elegans as pgph and its protein products has possessed G3PP activity, which is essential for the synthesis of glycerol [ 63 ]. The overexpression of phosphoglycolate phosphatase homolog-2 ( pgph-2 ) enhanced the conversion of Gro3P to glycerol, thereby reducing adipogenesis in nematodes.…”
Section: Regulation Of Fat Synthesis and Degradation In C E...mentioning
confidence: 99%